Sliding into Safety Net Participation: A Unified Analysis across Multiple Programs - Derek Wu; Jonathan Zhang (Institute of Labor Economics (IZA), 2023)
Recipients of government transfers are economically disadvantaged, yet little is known about how their circumstances evolve leading up to program receipt. Using twenty-five years of survey data as well as administrative health records, we establish three new stylized facts around enrollment in the largest safety net programs in the United States. While our focus is on SNAP, Medicaid, and Unemployment Insurance, the patterns generalize to nine major programs. First, market incomes decline around enrollment in almost all studied programs. Second, employment rates decline around program receipt and remain lower after receipt, with these patterns coinciding in part with increased disability and worse health. Third, spousal separations begin to increase prior to program enrollment, even for programs without mechanically related eligibility requirements. Taken together, these analyses provide a comprehensive and identically measured look across programs to demonstrate that households "slide" into safety net participation through multiple pathways.
Keywords: H53; I38; I18; 330; social insurance; means-tested transfers; welfare; program receipt